The Use of spotify as a Self-Learning Medium to Improve Listening Skills : A Case Study of Third-Semester TBI 2 Students - Deasy Yunita Siregar; Fika Mutiara Syahira; Aslimah Putri Rizky; Putri Afsila Cindy (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Listening skills are fundamental in English language learning because they are the main gateway to language proficiency. However, students often face obstacles such as differences in accents, the speed of native speakers, and limited vocabulary. This study aims to describe the use of the Spotify application as a learning medium to improve students' listening skills. This study uses a descriptive qualitative approach. The research subjects were third-semester students of the English Education Study Program at UIN Sumatera Utara (UINSU) in class TBI 2. Data were collected through questionnaires covering content usage patterns, duration, and application feature utilization. The results showed that: Students actively use Spotify (music and podcasts) as a source of authentic language input independently. Using Spotify has a positive impact on vocabulary comprehension, pronunciation, intonation, and conversation comprehension skills. The playback speed feature helps students control the audio speed according to their ability level, making the learning process more flexible and personalized. Consistent listening duration (15–30 minutes) is effective in supporting the development of listening skills without causing cognitive fatigue.